The Risk of Oil Fund Policy Globally. What about Ethics? - Veggeland, Noralv (European Scientific Journal, ESJ, 2017)
The systematic global market risk of the type found in the gigantic Norwegian Oil Fund, called “Government Pension Fund – Global (GPF – G)”, is discussed at length in this study. The objective is to find out if the risk capital animate ethical venture initiative. In the financial and entrepreneurial literature it has over time become common to relate systematic vulnerability and risk to a long range of factors that might cause imbalance and failure. Ulrich Beck (1992) postulates that risks today related to innovations and unethical and uncontrolled venture capital have a different significance for everyday life from the risks that applied to previous historical eras. He claims that human activity, innovation and technology in advanced political and economic modernity produce as a side-effect risks venturing investment. That demands specialised expertise to access and recognize, and are collective, global, and irreversible in their impact. To abstain from venturing actions are a way out of the dilemma for the investors. The Norwegian petroleum activity under regulatory management and control is an example of that. The Fund’s revenues have been shrinking lately following the oil prices of the market diving down globally. Perhaps the Norwegian Oil Fund is to be restructured in a framework of ethics to become less risk exposed in a global financial market perspective, and become more innovative and ethical directed.